Assessing and mitigating overheating risk in existing Canadian school buildings under extreme current and future climates - Mutasim Baba, Fuad (2022)
Canadian buildings have been primarily designed to withstand cold and long winters, not hot summers. With climate change and the increase in the intensity and severity of heatwaves, it has become important to investigate overheating in buildings. However, there are limited studies on assessing and mitigating the overheating risk in existing buildings that house vulnerable populations in cold climates, especially in Canada. This paper provides a framework for the systematic assessment of overheating risks and the development of passive mitigation strategies to reduce the overheating risks without increasing cool ing energy consumption under current and future climates with simulation models that are calibrated based on measured indoor air temperatures and outdoor weather conditions. The framework is applied to a school building built in 1958. The calibrated building model achieved an RMSE of less than 0.6 C compared with measurements, a Maximum-Absolute-Difference of less than 1.9 C, and a 1 C Percentage-Error of less than 10 %. The simulation results from the calibrated model predicted 110 over heating hours during the year 2020. The use of exterior blind roll or a combination of night cooling and other mitigation measures that reduce solar heat gain can achieve acceptable thermal conditions. In 2044 (the future extreme midterm year), night cooling with the exterior blind roll shading would be required during extreme heat events. Whereas during 2090 (the future long-term extreme year), additional mit igation measures such as a cool roof may be required to achieve an acceptable level of thermal conditions in the school.